CMOS die with LED display / Mohamad Nazruldin Razali and Khasrul Faizie Subbahi - Razali, Mohamad Nazruldin; Subbahi, Khasrul Faizie (2006)
These days there are much kind of games arc played on TV studios. Over 90% of required electronic equipment. The title of our project is a “ CMOS Die has LED display. Here’s a particularly elegant electronic dice design winch uses CMOS circuit for long batteries life. It also features automatic turnoff each “ throw “ is displayed. The read out is via a seven - LED display very similar to that of a normal die. Even with the inroads has made, games of skill and luck, where the element of chance provided by a die or pair of dice are still among the most popular recreations However, many arguments have been caused by the perchanl for normal dice to give apparently biased or ambiguos answer, particularly when the fever of the game is high.